Research on the intervention practice of the school physical education environment on the physical activity of college students - Chen, Li; Chiu, Yi-Hsiang (Nurture, 2023)
Purpose: This study discusses the main factors that affect the physical education environment of universities and college students’ physical activity levels. Design/Methodology/Approach: This study used the questionnaire method and the experimental method to conduct exploratory research on 286 college students (boys = 141, girls = 145) in eight teaching classes from new comers to senior students at Chongqing Normal University (one experimental class and one control class in each grade). Findings: The main factors of the school’s physical education environment were the interpersonal social environment, the natural physical environment and the physical education system environment. There was no significant statistical difference before the experiment. The experimental group showed statistical differences after the experiment. A substantial effect size was found in the intervention’s effectiveness tests (2 * 2 ANOVA) and (2 * 3 ANOVA). Conclusion: The school physical education environment can efficiently promote the improvement of the physical activity level of college students and the improvement effect has specific time persistence. The interpersonal social environment, the natural physical environment and the physical education system environment can be carried out when participating in the school’s physical education environment. Research Limitations: The limitation is that the experiment period needs to be longer. Practical Implications: Intervention practice can effectively improve college students’ physical activity through the school sports environment. Contribution to Literature: This paper explores a new way to promote college students’ physical exercise.